Principles of accounting : slide - Walgenbach, Paul Henry, 1923-; Dittrich, Norman E; Hanson, Ernest I; Harcourt Brace Jovanovich (New York : Harcourt Brace Jovanovich, 1976)
Provides a brief overview of principles in accounting.
Intended for use with book of same title by the same authors.
Sound accompaniment compatible for both manual and automatic operation.
Graphic, projected
Keywords: Accounting